1996
DOI: 10.1139/f96-092
|View full text |Cite
|
Sign up to set email alerts
|

The influence of habitat complexity and fish size on over-winter survival and growth of individually marked juvenile coho salmon (Oncorhynchus kisutch) in Big Beef Creek, Washington

Abstract: Wild juvenile coho salmon (Oncorhynchus kisutch) were individually marked in October 1990 and 1991 to evaluate the effects of habitat complexity and fish size on over-winter survival in Big Beef Creek, Washington. Habitat complexity was quantified for the habitat unit where the fish were collected and, in 1991, also for the 500-m reach downstream from the collection site. Survival, estimated from recovery of marked smolts at the stream's mouth, differed between years (25.4 and 46.2%) and also varied among habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
247
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(268 citation statements)
references
References 47 publications
17
247
4
Order By: Relevance
“…But these growth benefits are known to be rapidly offset by a reduction in the amount of critical overwintering instream cover and increasing fish mortality . BUSTARD and NARVER, 1975;RIMMER et al, 1983) and recruitment or early survival of some salmonid species (MORTENSEN, 1977;QUINN and PETERSON, 1996). Some authors have also reported the importance of cover in lowering the dispersal patterns and the extent of habitat range of fish populations (LEWIS, 1969;BJORNN, 1971;APARICIO and DE SOSTOA, 1999;HARVEY et al, 1999;RONI and QUINN, 2001a) reinforcing the hypothesis that the degree of structuring of habitats influences movement rates (BAADE and FREDRICH, 1998).…”
Section: Effects Of Cover Structures On Biological Productivitymentioning
confidence: 90%
See 1 more Smart Citation
“…But these growth benefits are known to be rapidly offset by a reduction in the amount of critical overwintering instream cover and increasing fish mortality . BUSTARD and NARVER, 1975;RIMMER et al, 1983) and recruitment or early survival of some salmonid species (MORTENSEN, 1977;QUINN and PETERSON, 1996). Some authors have also reported the importance of cover in lowering the dispersal patterns and the extent of habitat range of fish populations (LEWIS, 1969;BJORNN, 1971;APARICIO and DE SOSTOA, 1999;HARVEY et al, 1999;RONI and QUINN, 2001a) reinforcing the hypothesis that the degree of structuring of habitats influences movement rates (BAADE and FREDRICH, 1998).…”
Section: Effects Of Cover Structures On Biological Productivitymentioning
confidence: 90%
“…Rarely were abundances of benthic and drifting invertebrates jointly undertaken (ANGERMEIER and KARR, 1984;ELLIOT, 1986). Since the measure of fish density cannot account for the significance of cover for population dynamics, at least for territorial species such as salmonids, some authors have also marked individuals and used Capture-Marking-Recapture (CMR) for addressing the demographic mechanisms (growth, survival, or immigration) responsible for changes in population abundance or biomass with changes in cover structures (GOWAN and FAUSCH, 1996;QUINN and PETERSON, 1996;HARVEY 1998). In many instances, visual observation from the banks (BACHMAN, 1984) and by snorkelling (FAUSCH and WHITE, 1981;GRIFFITH and SMITH, 1993), or radiotelemetry (TODD and RABENI, 1989;YOUNG, 1995;ALLOUCHE et al, 1999;HARVEY et al, 1999) has allowed either counts or behavioural records.…”
Section: Assessment Of Biological Attributesmentioning
confidence: 99%
“…Increased boldness is correlated with body size in fish (Magnhagen & Staffan, 2003) and may result in increased growth (Sundström et al, 2004;Ward et al, 2004). Body size also has consequences for an individual's survival and fitness (Quinn & Peterson, 1996;Werner & Gilliam, 1984), explaining why larger bold feeders are observed in some populations. However, there are costs as well as benefits associated with being larger and bolder.…”
Section: Biological Correlatesmentioning
confidence: 99%
“…Rapidly developing embryos may have more access to resources, because they emerge from the gravel first and have more opportunity for feeding early in the season, resulting in larger size as fry (Beacham et al, 1988;Einum and Fleming, 2000). Greater size at the fry stage is positively correlated with freshwater overwintering survival (Quinn and Peterson, 1996). However, when predation is density dependent, early development and corresponding high growth rates as fry may increase an individual's exposure to predation risk and result in lower fitness (Sundstrom et al, 2005).…”
Section: Introductionmentioning
confidence: 99%